Pengaruh Disiplin Kerja, Karakteristik Pekerjaan Dan Motivasi Terhadap Kinerja Pegawai Perusahaan Umum Daerah Pasar Kota Medan - Silitonga, M. Chocky Oktalion; Chandra, Dody Salden (Lembaga Riset Ilmiah, 2022)
The purpose of this study was to determine the effect of work discipline on employee performance at the Medan City Market Regional Public Company, to determine the effect of job characteristics on employee performance at the Medan City Market Regional Public Company, to determine the effect of motivation on employee performance at the Medan City Market Regional Public Company. and to determine the direct effect of work discipline, job characteristics, and motivation on employee performance at the Medan City Public Company. This study uses an associative research approach. The number of samples in this study was 96 respondents using saturated samples. The data collection technique in this study was using a questionnaire or questionnaire distributed to employees of the Medan City Market Public Company. The data analysis technique used multiple linear regression, classical assumption test, t-test, f-test, and coefficient of determination. Based on the results of the study, it can be concluded that work discipline has a positive and significant effect on employee performance at the Medan City Public Public Company. Job characteristics have a positive and significant impact on employee performance at the Medan City Market Public Company. Motivation has a positive and significant influence on the performance of employees at the Regional Public Company Pasar Medan City. Simultaneously work discipline, work characteristics, and work motivation have a positive and significant influence on employee performance at the Medan City Public Company